Characterization and phylogenetic analysis of the complete mitochondrial genome of Terapon theraps (Perciformes: Terapontidae) - Lei Zeng; Pimao Chen; Jie Yu; Guobao Chen (Mitochondrial DNA. Part B. Resources, 2021)
We assembled the complete mitochondrial genome of Terapon theraps based on high-throughput Illumina sequencing. The mitochondrial genome of T. theraps is 16,587 bp in length, containing 13 protein-coding genes (PCGs), 22 tRNAs, two rRNAs, and one putative control region (CR), and its overall nucleotides base composition is 27.4% A, 25.7% T, 16.9% G, and 29.9% C. Bayesian Inference revealed that all species of Terapontidae formed into one group, while the other nine species within Perciformes clustered into the other group. Rhynchopelates oxyrhynchus and T. theraps were the closest relatives. These results should help to better understand the phylogenetic interrelationships of Terapontidae.